Living with Leopard-Utopia or reality! Study on perception of local people towards coexistence with Leopard (Panthera pardus fusca) in and around the vicinity of the urban areas of Central India - Aniruddha Majumdar; Tanuj Suryan; Balram Lodhi; Anjana S. Tirkey; Abhay Kumar Patil; Ravindra Mani Tripathi; Shakti Shukla; Jashndeep Singh Thakur; Amit Kumar Jaiswal; Jasti Sai Krishna (Universitas Pakuan, 2025)
Study on people’s perception towards human & leopard coexistence in urban landscape was conducted from April 2022 to March 2023 at Jabalpur and Indore, Madhya Pradesh. In total, 73 villages and 2,827 households were surveyed in the urban areas of Jabalpur, whereas 48 villages and 2,255 households were surveyed in the urban areas of Indore through a standard structured questionnaire. The present study revealed a higher frequency of reported leopard encounters in Indore as compared to Jabalpur. Despite similar concerns in both study areas about the threats posed by leopards and the need for conservation, significant differences were found in respondents’ willingness to learn about leopards and to coexist with them. Respondents in both Jabalpur and Indore predominantly attributed leopard presence to deforestation and forest land diversion. Despite their fear of living with large carnivores, a majority of participants indicated that they would not harm a leopard if encountered. Respondents from Indore reported higher satisfaction with the forest department's conservation efforts, possibly due to quicker compensation payments as compared to Jabalpur and also because they have exhibits (zoological park) of leopards and other wildlife for common people. During the survey, lack of awareness about conservation of leopard was observed in the periphery of urban landscape. Hence, running conservation awareness programmes with the help of NGOs and civil societies on human-leopard coexistence in both of these study areas may greatly help reduce hatred towards leopard in and around urban areas.